Legitimacy of consumer associations and perceived vulnerability of their users: Effects on intentions to trust consumerist associations. (March 2018) - Lichtlé, Marie-Christine; Nabec, Lydiane; Roux, Dominique; Chevalier, Corinne
The trust that people place in consumer associations to protect their interests in dealing with commercial entities is at the heart of the consumerist mission. It is therefore important to identify the factors underpinning this trust. The results of one qualitative study (51 respondents) and one quantitative study (315 individuals) reveal that intentions to trust a consumer association depend on its recognized degree of cognitive, pragmatic and moral legitimacy. Furthermore, the effect of pragmatic legitimacy on such intentions varies in accordance with the perceived vulnerability of consumers in dealing with commercial entities. However, perceived vulnerability does not moderate the relationship between cognitive and moral legitimacy and intentions to trust consumer associations: it has a direct influence on this response variable.